E-Government Implementation in Nigeria: Exploring Panacea for Good Governance - Mohammed W. Kirfi, Musa; Abdulrasaq Ajadi, Ishola (Kashere Journal of Humanities, Management and Social Sciences, 2022)
The foremost indication of good governance begins with an efficient and effective social service delivery by the state apparatus. This in return calls for the prompt payment of taxes and dues on the part of the citizens. There is a growing consensus that e-government can facilitate a symbiotic relationship with good governance as it is at the heart of an effective and efficient public service delivery and citizens’ engagement. Third world nations prominent among which is Nigeria lay claims to e-government adoption without a significant improvement in the quality and medium of social service delivery. Where lays the reason for this backdrop in the result? Using the United Nations Department of Economic and Social Affairs (UN-DESA) 5-Stage web maturity model, this paper evaluates the websites of eight (8) purposively selected Federal Agencies’ service portals that constituted the foremost online public service delivery agencies in Nigeria to ascertain the extent of e-Government implementation in the country. Through the domestication of web measurement index of UN-DESA, the study found that all the selected agencies had an average score of 100% at the emerging stage and 50% at the enhanced stage. The agencies had 83.4% at the interactive stage while at the transactional stage; only the Corporate Affairs Commission (CAC) met the minimum requirement of the stage by recording 60%, while none of the forefront federal agencies selected for this study met the minimum requirement of the connected stage of e-government implementation. The paper thus concluded that e-government implementation in Nigeria is haphazard because not all the selected agencies fulfilled the requirements in many of the stages before embarking on the features on the next stages. However, the implementation is beyond the interactive stage, and yet to be established at the Transactional stage.